Physiologic intracranial calcification with hyperintensity on MR imaging: case report and experimental model. - Dell, L A; Brown, M S; Orrison, W W; Eckel, C G; Matwiyoff, N A (American Journal of Neuroradiology, 1988)
CT and MR imaging showed basal ganglia calcification that appeared as high signal intensity on T1-weighted images of a patient with pseudohypoparathyroidism. MR imaging of an experimental model of calcium phosphate suspensions showed a signal similar to that seen in the patient. Additionally, T1 and T2 relaxation times of the solutions were measured and showed decreases in both parameters with increasing calcium phosphate concentrations. Intracranial calcification can appear as high signal intensity on T1-weighted images. An experimental model shows that the calcium salt decreases the T1 of surrounding water. Therefore, calcium, and possibly other elements, may induce paramagnetic susceptibility effects.